2008
DOI: 10.1192/bjp.bp.107.040824
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for people bereaved through suicide: systematic review

Abstract: Although there is evidence of some benefit from interventions for people bereaved by suicide, this is not robust. Further methodologically sound evidence is required to confirm whether interventions are helpful and, if so, for whom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 13 publications
0
85
0
5
Order By: Relevance
“…Qualitative interviews with British general practitioners indicate that although the majority feel a responsibility to contact bereaved patients, particularly after traumatic bereavement (41), many feel unprepared to deal with the specific effects of suicide, welcoming guidance on what approach to take (42). Their uncertainty is compounded by a lack of evidence for effective interventions to reduce the risk of suicide and psychopathology (13). Each suicide affects a network of relatives, former partners, and friends (3) that extends well beyond registered next of kin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative interviews with British general practitioners indicate that although the majority feel a responsibility to contact bereaved patients, particularly after traumatic bereavement (41), many feel unprepared to deal with the specific effects of suicide, welcoming guidance on what approach to take (42). Their uncertainty is compounded by a lack of evidence for effective interventions to reduce the risk of suicide and psychopathology (13). Each suicide affects a network of relatives, former partners, and friends (3) that extends well beyond registered next of kin.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative work would permit a deeper exploration of the acceptability and quality of support received. Given the limited evidence base, further trials are required of interventions for people bereaved by suicide (13), particularly proactive outreach, for which there is an expressed need (44). Primary care and psychiatric professionals are in unique positions to offer such outreach and to counter reluctance to seek help.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 It is not clear what interventions are effective because evidence is currently limited 13 but it is suggested that specialist bereavement counselling can be useful for those actively seeking it.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] GPs were unclear on what can be offered to those bereaved or the efficacy of available interventions, and the evidence in the literature is similarly unclear. 13 One mentioned that they offered a hug to their patient, and others talked of the importance of face-to-face encounters. The literature suggests that 'touch' can be useful in certain clinical encounters to comfort and connect with patients.…”
mentioning
confidence: 99%
“…With limited evidence to substantiate the effectiveness of traditional western based grief theories, these models have been comprehensively utilised in grief therapy without accommodating western and non-western cultural responses to bereavement (Valentine, 2006). Moreover, postvention activities formulated from a western philosophical framework can be ineffective in addressing the needs of culturally diverse groups who may require more culturally appropriate interventions reflecting their cultural background (McDaid, Trowman, Golder, Hawton, & Sowden, 2008). According to Rothaupt & Becker (2007), understanding normal and adaptive responses to grief within different cultural contexts is important in generating knowledge within this area.…”
Section: Key Factors Affecting Grief Reactionmentioning
confidence: 99%